Data from: breeding under pressure: corticosterone is associated with reproductive investment under fluctuating predation risk in a long-lived sea duck ... - Mohring, Bertille; Öst, Markus; Jaatinen, Kim; Parenteau, Charline; Grimaud, Emmanuelle; Angelier, Frédéric (Dryad, 2023)
Phenotypic plasticity may enable individuals to cope with predictable and unpredictable environments during their life-cycle. In that context, studying glucocorticoids – corticosterone (CORT) in birds – is relevant because of their primary role in allostasis. Higher baseline CORT levels are classically associated with environmental constraints and lower fitness (the CORT-fitness hypothesis). However, in some environments, higher baseline CORT levels can promote reproduction, therefore being associated with higher fitness (the CORT-adaptation hypothesis). These two hypotheses have been tested in multiple systems, but rarely in a context of fluctuating predation threat. We used a long-term individual-based monitoring of baseline CORT levels in female common eiders Somateria mollissima (nCORT = 1537; nindividual = 790; 2009-2022) to disentangle the context-dependent links between environmental conditions, CORT and fitness. Importantly, the study population has been facing a drastic increase in predation ... : # Breeding under pressure: corticosterone is associated with reproductive investment under fluctuating predation risk in a long-lived sea duck [https://doi.org/10.5061/dryad.xd2547dpj](https://doi.org/10.5061/dryad.xd2547dpj) **Authors:** Bertille Mohring1,2, Markus Öst1,3, Kim Jaatinen4,5, Charline Parenteau2, Emmanuelle Grimaud2, Frédéric Angelier2 1Environmental and Marine Biology, Åbo Akademi University, 20500 Turku, Finland 2Centre d’Etudes Biologiques de Chizé, UMR 7372 CNRS – La Rochelle Université, 79360 Villiers-en-Bois, France 3Novia University of Applied Sciences, 10600 Ekenäs, Finland 4Nature and Game Management Trust Finland, 10160 Degerby, Finland 5Tvärminne Zoological Station, University of Helsinki, 10900 Hanko, Finland ## Description of the data and file structure Four datasets have been used in this paper, and the variables are detailed below and a broader description of the data is available in the paper. **Dataset 1 (dataset_CORT.csv): Intrinsic and extrinsic determinants of female ...